2012
DOI: 10.1097/iae.0b013e3182509796
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Manifestations of Syphilitic Uveitis in Chinese Patients

Abstract: Posterior uveitis was the most common ocular finding in these investigated Chinese patients with syphilis. Coinfection of syphilis and human immunodeficiency virus was less common in these patients. Syphilis should be considered in the differential diagnosis of patients presenting with large iris granulomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
55
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 31 publications
7
55
1
Order By: Relevance
“…An overall good visual prognosis in syphilitic uveitis such as found in this large cohort confirms previous studies. [6][7][8][9][10][11] In our study, a higher logMAR VA at the start of syphilis treatment and a delay of more than 12 weeks between the first presentation of uveitis and treatment for syphilis were associated with a statistically significantly higher logMAR VA at 6 months. Possible reasons for diagnostic delay include patients' and doctors' delay.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…An overall good visual prognosis in syphilitic uveitis such as found in this large cohort confirms previous studies. [6][7][8][9][10][11] In our study, a higher logMAR VA at the start of syphilis treatment and a delay of more than 12 weeks between the first presentation of uveitis and treatment for syphilis were associated with a statistically significantly higher logMAR VA at 6 months. Possible reasons for diagnostic delay include patients' and doctors' delay.…”
Section: Discussionmentioning
confidence: 55%
“…Previous studies on prognostic factors in ocular syphilis 6,16,17 showed no difference in visual outcome when comparing the ''classic'' regimen of intravenous penicillin with other antibiotics. But, these studies 6,16,17 were all in small groups, with different kinds of antibiotics and therefore the results should be interpreted cautiously.…”
Section: <0001mentioning
confidence: 99%
“…All manifestations resolved between 2 and 3 weeks after initiation of the treatment (7) . Yang et al (8) described a Chinese patient who presented mutton fat precipitates in the posterior vitreous membrane with retinal vasculitis in both eyes. In addition, Yang and colleagues described three other eyes in two patients, which presented multiple perimacular whitish dots termed as "multiple punctiform retinian precipitates", (8) very similar to those found in our cases.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al (8) described a Chinese patient who presented mutton fat precipitates in the posterior vitreous membrane with retinal vasculitis in both eyes. In addition, Yang and colleagues described three other eyes in two patients, which presented multiple perimacular whitish dots termed as "multiple punctiform retinian precipitates", (8) very similar to those found in our cases. Our study, as suggested by these authors, indicates that these precipitates or pale yellowish dots are highly suggestive of ocular syphilis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation